Behavioral Innovations to Access Abortion Post-Dobbs: A Qualitative Thematic Analysis of Reddit’s r/abortion Community in 2022 - Eliza Dolgins BA; Lindsay Parham PhD, JD; Karen Weidert MPH; Emma Anderson MPH; Coye Cheshire PhD, MA; Ndola Prata MD, MSc; Elizabeth Pleasants DrPH, MPH (Inquiry: The Journal of Health Care Organization, Provision, and Financing)
Following the leak of the Dobbs decision in 2022, abortion access in the United States has faced heightened barriers, including legal restrictions, financial constraints, and logistical challenges. In response, individuals seeking abortion care can employ innovative behavioral strategies to overcome these barriers and reshape their abortion experiences (ie, “behavioral innovations”). This paper explores the behavioral innovations to access abortion that people discussed and recommended within a geographically dispersed community of peers on an abortion-supportive Reddit community (r/abortion). Using a hybrid inductive and deductive thematic qualitative analysis approach with a purposive sample of comments in the r/abortion community in 2022 following the Dobbs leak (May-December, n = 131 comments), we identified discussion of abortion access innovations related to getting in-clinic care, self-managed abortion (SMA), funding assistance, privacy, and emotional support. Innovations included sharing online resources for clinic locations, specific travel recommendations to less restrictive states, accessing abortion medications through online services, and navigating the SMA process. Additionally, other less tangible innovations were discussed, including strategies for keeping abortions private and seeking emotional support. Our findings highlight how individuals within the r/abortion community discuss and share creative strategies for navigating the evolving barriers to abortion care. The r/abortion platform serves as a crucial resource for individuals seeking innovative solutions to these barriers, underscoring the need for diverse information-sharing practices to improve access to care as shifting legislation increasingly demands approaches beyond conventional norms.